Study of improved cavity resonant reflector for an X-Band relativistic backward wave oscillator - Ansari M.A.; Thottappan M. (My University, 2025)
The RF breakdown is a key issue in Relativistic Backward Wave Oscillator (RBWO) at the GW level of power and it can be overcome by opting an overmoded Slow Wave Structure (SWS) or an overmoded cavity Resonant Reflector (RR) or both. An overmoded rectangular cavity RR and trapezoidal cavity RR are designed and analyzed for an axial electric field variation inside, using an eigenmode simulation of MAGIC-3D. The strength of axial electric field around the surface of an overmoded rectangular and trapezoidal cavity RR is found to be around ~800kV/cm and ~500kV/cm respectively as compared to the conventional rectangular cavity RR around ~1MV/cm. Further PIC simulation of nonuniform RBWO with these cavities RR is performed and compared with the results reported with conventional rectangular cavity RR. © 2018 IEEE.